Penggunaan Alih Kode dan Campur Kode dalam Film Kaka Bos: Representasi Budaya Pop dan Identitas Digital - Pangestu, Berlian Ayu (Program Studi Magister Linguistik Terapan UNJ, 2025)
This study aims to analyze the use of code-switching and code-mixing in the film Kaka Bos as a representation of pop culture and digital identity. Using a descriptive-qualitative linguistic approach, the research examines how these linguistic phenomena reflect the identity dynamics of the digital generation and the influence of pop culture in daily interactions. Data were collected from film dialogues containing code-switching and code-mixing between Indonesian, regional languages, and foreign languages (particularly English). The results indicate that the use of these phenomena serves not only as a communication tool but also as an identity strategy to assert connections with global culture while maintaining locality. These findings provide insights into how popular media like films represent linguistic hybridity and identity in the digital era.